National Interest Organizations in the EU Multilevel System - Eising, Rainer (West European Politics, 2018)
Political scientists have always accorded interest organizations a prominent place in European Union (EU) policy-making because they connect the EU institutions to citizens, provide important information to EU policy-makers, and control resources that impact on the problem-solving capacity of EU policies. In other words, they are vital to both the input legitimacy and the output legitimacy of the EU. So far, research on interest organizations in EU policy-making has concentrated on EU-level interest organizations and EU-level politics. This edited book draws attention to the role national interest organizations play in the EU multilevel system. All contributions present state-of-the-art research on that subject in the form of theory-driven empirical analyses. The ten chapters indicate that national interest organizations have adapted to the EU's multilevel polity in terms of their strategies; their relations with parliaments, governments, and the EU institutions; as well as their collaboration with EU umbrella organizations. Especially, they offer new insights into the alignments among national interest organizations and decision-makers, the Europeanisation of these organizations in established EU member states and candidate countries, and the existence of bias in national and EU interest group populations. The chapters in this book were originally published in a special issue of West European Politics.